Efficacy and safety of ciprofloxacin, eye ointment and eye drops, 0.3 %, in modern therapy of infectious and inflammatory eye diseases. A review - A. V. Trubilin; E. G. Polunina; E. A. Serebryannikova; A. G. Iksanova; T. D. Ustinova (Российский офтальмологический журнал)
Bacterial conjunctivitis is the main reason for patients to visit ophthalmologists, and the incidence is high among both children and adults. In the current version of the Clinical Guidelines for the section “Conjunctivitis”, approved by the Scientific and Practical Council of the Ministry of Health of the Russian Federation, antibacterial and antiseptic agents are recommended as etiotropic therapy for the treatment of infectious conjunctivitis (bacterial, chlamydial) or in case of suspicion/prevention of secondary bacterial infection in conjunctivitis of other etiologies with antibacterial purposes. Antibacterial agents in the dosage form of eye drops are represented by the following International Nonproprietary Names (INN): ofloxacin, ciprofloxacin, levofloxacin, moxifloxacin, netilmicin, tobramycin, chloramphenicol, in the dosage form of eye ointments: INN tetracycline, erythromycin, tetracycline + chloramphenicol. Of the antiseptic agents, eye drops are presented with the INN picloxidine and benzyldimethyl-myristoylamino-propylammonium. Thе review presents the comparative efficacy and safety of ciprofloxacin eye drops and ointment, as well as on the assessment of their clinical significance in the treatment of bacterial eye infections.